(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Consumer varied behaviour constitutes a relatively incipient research line in the marketing field, with potential to provide useful managerial guide lines for retailers. For this reason, in this paper, a state of the art on consumer varied behaviour is presented.In short, we intend to describe the definitions of the different used terms, as well as the different application contexts and the consequent implications for the managers of the firms operating in the retailing sector. Besides, the main conclusions derived from the critical review of the literature realised and proposals for the developmentof future research lines are provided.